(NmETODIKA NAW^ANNQ ANGL)QÆJSXKOÇ MOWI W PO^ATKOWÆJ [KOLÆ (B:s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (NbABENKO(B, (NtAMARA wASIL)QÆWNA(B,s)E; (NkI)QÇWSXKIJ NACÆONALXNIJ UNÆWERSITET ÆMENÆ tARASA {EW^ENKAs)E ((NkI)QÇW (B:s)E (NaR)QÆSTEJ(B,s)E, 2005)
(Nu NAW^ALXNOMU POS)QÆBNIKU ROZGLQDA@TXSQ NAJBÆLX[ AKTUALXNÆ PITANNQ METODIKI NAW^ANNQ ANGLÆJSXKOÇ MOWI U PO^ATKOWÆJ [KOLÆs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpEDAGOG)QÆKAs)E -- (NmETODIKA WIKLADANNQs -- (NaNGL)QÆJSXKA MOWAs)E